Anionic Sites and the Mechanisms of Proteinuria - Cotran, Ramzi S; Rennke, Helmut G (The New England journal of medicine, 1983)
Proteinuria is the hallmark of glomerular injury, and the study of its mechanisms remains a subject of considerable interest. In recent years, physiologic, ultrastructural, immunochemical, and biochemical techniques have established the importance to normal glomerular structure and permeability of negatively charged molecular groups in the glomerular basement membrane — the so-called glomerular anionic sites or polyanions. Histochemists have long known that the glomerulus is rich in anionic sites, since it stains strongly with such polycationic reagents as colloidal iron and alcian blue. Indeed, a role for polyanions in glomerular permeability was suggested by Michael et al. in 1970 on the . . .